Результаты исследований поселения Уч-Баш в 2006—2008 гг. - Савеля, О.Я.; Кравченко, Э.А.; Лысенко, Р.В.; Филиппенко, А.А.; Шевченко, Д.А. (Археологічні дослідження в Україні, 2009)
The paper is a preliminary publication of archaeological research at Uch-Bash settlement in the South-Western Crimea, provided by the National Preserve «Tauric Chersonesos» and the IA NASU.